2017
DOI: 10.1016/j.drugpo.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Unintended impacts of regulatory changes to British Columbia Methadone Maintenance Program on addiction and HIV-related outcomes: An interrupted time series analysis

Abstract: Background In February 2014, several regulatory reforms were introduced to the methadone maintenance treatment (MMT) program in British Columbia, Canada, including a switch to a ten-times more concentrated methadone formulation and restrictions in pharmacy delivery services. We evaluated possible unintended effects of these changes on illicit drug use patterns and HIV treatment outcomes among HIV-positive opioid users. Methods Data was drawn from ACCESS, a prospective community-recruited cohort of HIV-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(49 reference statements)
2
10
0
Order By: Relevance
“…While this is encouraging, it should be noted that after a steady increase in the proportion of participants meeting each of the cascade stages between 2006 and 2014, we observed a declining trend in the last two years of the study period. This worsening of cascade indicators occurred after regulatory changes to the BC OAT program in February 2014, and are consistent with prior research (McNeil et al, 2015; Socias et al, 2017). Specifically, both quantitative and qualitative studies demonstrated interruptions in OAT and co-dispensed medications (e.g., antiretroviral therapy) following restrictions on pharmacy delivery services, as well as increases in injection opioid use, which might be explained by “change intolerance” to the new methadone formulation experienced by some OAT clients (McNeil et al, 2015; Socias et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While this is encouraging, it should be noted that after a steady increase in the proportion of participants meeting each of the cascade stages between 2006 and 2014, we observed a declining trend in the last two years of the study period. This worsening of cascade indicators occurred after regulatory changes to the BC OAT program in February 2014, and are consistent with prior research (McNeil et al, 2015; Socias et al, 2017). Specifically, both quantitative and qualitative studies demonstrated interruptions in OAT and co-dispensed medications (e.g., antiretroviral therapy) following restrictions on pharmacy delivery services, as well as increases in injection opioid use, which might be explained by “change intolerance” to the new methadone formulation experienced by some OAT clients (McNeil et al, 2015; Socias et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…This worsening of cascade indicators occurred after regulatory changes to the BC OAT program in February 2014, and are consistent with prior research (McNeil et al, 2015; Socias et al, 2017). Specifically, both quantitative and qualitative studies demonstrated interruptions in OAT and co-dispensed medications (e.g., antiretroviral therapy) following restrictions on pharmacy delivery services, as well as increases in injection opioid use, which might be explained by “change intolerance” to the new methadone formulation experienced by some OAT clients (McNeil et al, 2015; Socias et al, 2017). Importantly, had a quality improvement framework (e.g., cascade of care) been in place (Clarke et al, 2016), it may have facilitated early identification of the worsening of cascade indicators, interventions to prevent attrition, and potentially averted some of the overdose deaths observed during this period.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another potential significant contributor to dissatisfaction is the regulatory change in British Columbia introduced in 2014 to the Methadone Maintenance Program, which involved changing the methadone formulation [26]. Previous studies reported significant increases in the prevalence of heroin injection and opioid withdrawal symptoms following this regulatory change in our setting [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Another recently published study assessed patterns of changes in injecting frequency in a European population and found similar longitudinal patterns , but the overall decreasing trend was not as strong as in the ALIVE cohort. In the face of escalating harmful illicit drug use, harm‐reduction interventions, including needle and syringe programs , supervised consumption facilities and methadone maintenance therapy , have been implemented and scaled‐up in British Columbia, Canada. However, to our knowledge, there exist no studies that have examined the longitudinal trajectories of injection drug use in a Canadian setting.…”
Section: Introductionmentioning
confidence: 99%